Kelayakan Bahan Ajar Teks Negosiasi Berbasis Etnis Batak Simalungun Berbantuan Aplikasi untuk Meningkatkan Pembelajaran Kelas X SMK PAB 5 Klambir Lima - Rika Kartika; Heri Setiawan (Departement of Mathematics Education, 2022)
This study aimed to describe the process of Appropriateness, validation, feasibility, and effectiveness of using Simalungun ethnic-based teaching materials with application-assisted applications on negotiating text materials for class X SMK. This study was conducted in SMK PAB 5 Klambir V. The research method is Research and Development (R&D) with a 4D model including Definition, Design, Development, and Dissemination with a population as 48 students. This study used a purposive sampling technique with a total of 23 students. The types of data include qualitative and quantitative data. The result of the study is a product of teaching materials in the form of a textbook based on Simalungun Batak ethnic. According to the results of the material expert validation, validator I as 75%, and validator II as 98%. While the results of validation by design experts are validator I as 96%, and validator II as 84%. These data indicated that the teaching materials are valid and feasible to be tested in schools. The materials were tested in SMK PAB 5 Klambir V with a class X TKJ-2 as the sample, the teacher's response was 92%. The data were obtained from questionnaires consisting of the results of a small group trial categorized as